Clinical trials to gene therapy development and production in Brazil: a review - Jonas Alex Morales Saute; Virginia Picanço-Castro; Ana Carolina de Freitas Lopes; João Batista da Silva Júnior; Johanna Henriques Nehm; Franciele dos Santos Maciel; Ida Vanessa Doederlein Schwartz; Juliana Maria Ferraz Sallum; Margareth Castro Ozelo; Roberto Giugliani; Martin Bonamino; Hilda Petrs-Silva; et al. (The Lancet Regional Health. Americas)
Summary: Challenges related to the implementation of gene therapy products are daunting for low-to middle-income countries, such as Brazil, and include the creation of an appropriate technical, regulatory, and economic environment. In this manuscript, we give an overview of historical aspects, as well as the current state of clinical trials and approved gene therapy products for commercialization in Brazil. Focusing on gene replacement and CAR-T cell therapies, we discuss the main advances, limitations, and difficulties faced by the country in the production, approval, and incorporation of such products into the public health system. Finally, we highlight the potential leading role that low-to middle-income countries can have in this industry, not only by providing their own vector supply but also by addressing important issues related to the sustainability and long-term global affordability of gene therapy products.